1970
DOI: 10.3329/bjm.v24i1.1245
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Forty Higher Plants against Phytopathogenic Fungi

Abstract: Every year a lot of crop damage is caused by various diseases and among them fungal diseases are very common [1][2] . Although the use of synthetic fungicides in plant disease control have shown its fruitfulness in the improvement of agriculture, several of these have been found to display side-effects in the form of carcinogenicity, detrimental effects and other residual toxicities. The alternative choice therefore would be the use of botanical fungicides, which are advocated to be largely non-phytotoxic, sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…From the investigation, it was observed that leaf extract of Piper betel in ethanol and acetone at 20% concentrations effectively suppressed the mycelial growth of the F. oxysporum. Inhibition observed by P. betel may be due to the presence of the essential oils which contained phenolic compounds [16] [17]. There have been reports on the antifungal activities of P. betle [18].…”
Section: Resultsmentioning
confidence: 99%
“…From the investigation, it was observed that leaf extract of Piper betel in ethanol and acetone at 20% concentrations effectively suppressed the mycelial growth of the F. oxysporum. Inhibition observed by P. betel may be due to the presence of the essential oils which contained phenolic compounds [16] [17]. There have been reports on the antifungal activities of P. betle [18].…”
Section: Resultsmentioning
confidence: 99%
“…The ethanolic extract of several higher plants could be used as alternative source of antifungal agents for protection of plants or crops against fungal infection. [34] Antibacterial Activity …”
Section: Anti-seizures Activitymentioning
confidence: 99%
“…Fresh leaves are reported to have antioxidant properties [2,6]. Mild antibacterial and antifungal properties are also shown by the ethanol extract of the whole plant [7]. The valuable medicinal plant P. foetida is under stress in its natural habitat due to anthropogenic activities such as unsustainable harvesting by local medical practitioners, deforestation, urbanization, and habitat fragmentation [8].…”
Section: Introductionmentioning
confidence: 99%